BIOFILM AND TUMOR: INTERPRETATION OF INTERACTION AND TREATMENT STRATEGIES. Review - N. Ivanenko (Медична наука України, 2021)
Relevance. Treatment of solid tumors and biofilm-derived infections face a common problem: drugs often fail to reach and kill cancer cells and microbial pathogens because of local microenvironment heterogeneities. There are remarkable challenges for current and prospective anticancer and antibiofilm agents to target and maintain activity in the microenvironments where cancer cells and microbial pathogens survive and cause the onset of disease. Bacterial infections in cancer formation will increase in the coming years. Collection of approaches such as ROS modulation in cells, the tumor is promoted by microbe’s inflammation can be a strategy to target cancer and bacteria. Besides that, bacteria may take the advantage of oxygen tension and permissive carbon sources, therefore the tumor microenvironment (TM) becomes a potential refuge for bacteria. It is noteworthy that the relationship between cancer and bacteria is intertwined.